Assessing outcomes of educational videos in group visits for patients with chronic pain at an academic primary care clinic. Issue 5 (4th July 2017) - Vogler, Carrie N.; Sattovia, Stacy; Salazar, Laura Y.; Leung, Tiffany I.; Botchway, Albert
ABSTRACT: Objectives : This study evaluates the impact of pain education group visits on patients with chronic non-cancer pain (CNCP). The primary outcome of the study was to evaluate patients' functional status and secondary outcomes included knowledge, behavior, and satisfaction, before and after participation in the pain education group visits. Methods : Locally produced patient educational videos on chronic non-cancer pain were delivered during patient group visits led by a healthcare provider. Study participants included patients with CNCP pain in an academic general medicine practice. The primary outcome was functional status, measured by the Pain Intensity, Enjoyment of life, and General Activity (PEG) score and the Oswestry Disability Index. Secondary outcomes were evaluated through a pre- and post-intervention knowledge assessment and chart review of opioid use and utilization of emergency and urgent care services. A satisfaction survey was administered after each group visit. Results : Thirty-five patient-group visits were analyzed and 14 patient charts reviewed. A moderately positive correlation was observed between PEG and Oswestry Disability Index (r = 0.47, p < 0.05). Patient knowledge improved after watching the videos and participating in group discussion. The median amount of daily morphine equivalents for patients (n = 14) was 17.5mg (range 0-120mg) at the first study, and decreased to 12.5mg (range 0-110mg) at the last study visit (p = 0.39). None of the 14 patients utilized emergency or urgent care services for pain during the study. Overall, patient satisfaction scores with the intervention were high. Conclusion : Group visits providing patient education about CNCP may benefit patients' knowledge about this clinical condition, and was received with high patient satisfaction. Further investigation is needed to evaluate longer-term knowledge retention, sustainability of improvements resulting from the intervention, and longer-term effects of the intervention on functional status.